Mercenaries in the eastern Mediterranean from the late Bronze Age to the Iron Age - Ringheim, HL (2018)
The thesis investigates the presence of mercenaries in the Eastern Mediterranean, specifically in Egypt and the Levant, from the Late Bronze Age to the end of the sixth century B.C.E. The time frame predates the ubiquitous mercenaries of the Classical period onwards, and traces the origins of the profession and how it manifested in the archaeological record. The examination begins with the earliest evidence for non-local contingents hired in armies during the Bronze Age, based on the sources and archaeological remains, in order to address how to define mercenaries in antiquity. From these instances, the thesis posits a new definition for mercenaries in antiquity that encompasses the activities and characteristics of such foreign groups. The investgation then turns to the Iron Age, when the contemporary sources are scarce, but the archaeology is telling of numerous calamitous, historical events that precipitate the need for mercenaries. Past scholarship argued that specific sites in the Iron Age Levant and in Egypt exemplify evidence of mercenary activity, based primarily on different ceramic repertoires. An evaluation of the case studies reassesses whether this is indeed the case; how do the archaeological remains function as indicators of mercenaries? What factors are revealing of nonlocal contingents situated in a different context? The material remains, and whether they indicate non-local cultural practices and activities, are investigated. By considering the available remains, in addition to the ceramics, including architecture, burial rites, ritual practices, weapons, and the contexts in which the finds are discovered, it is then possible to assess where and when mercenaries are traceable. The discoveries and interpretations from the thesis shed light on archaeological indicators for mercenary activity, and which sites suggest such evidence, and which do not.